Postnatal nutritional restriction affects growth and immune function of piglets with intra-uterine growth restriction. Issue 1 (10th June 2015) - Hu, Liang; Liu, Yan; Yan, Chuan; Peng, Xie; Xu, Qin; Xuan, Yue; Han, Fei; Tian, Gang; Fang, Zhengfeng; Lin, Yan; Xu, Shengyu; Zhang, Keying; et al.
Abstract : Postnatal rapid growth by excess intake of nutrients has been associated with an increased susceptibility to diseases in neonates with intra-uterine growth restricted (IUGR). The aim of the present study was to determine whether postnatal nutritional restriction could improve intestinal development and immune function of neonates with IUGR using piglets as model. A total of twelve pairs of normal-birth weight (NBW) and IUGR piglets (7 d old) were randomly assigned to receive adequate nutrient intake or restricted nutrient intake (RNI) by artificially liquid feeding for a period of 21 d. Blood samples and intestinal tissues were collected at necropsy and were analysed for morphology, digestive enzyme activities, immune cells and expression of innate immunity-related genes. The results indicated that both IUGR and postnatal nutritional restriction delayed the growth rate during the sucking period. Irrespective of nutrient intake, piglets with IUGR had a significantly lower villous height and crypt depth in the ileum than the NBW piglets. Moreover, IUGR decreased alkaline phosphatase activity while enhanced lactase activity in the jejunum and mRNA expressions of Toll-like receptor 9 ( TLR-9 ) and DNA methyltransferase 1 ( DNMT1 ) in the ileum of piglets. Irrespective of body weight, RNI significantly decreased the number and/or percentage of peripheral leucocytes, lymphocytes and monocytes of piglets, whereas the percentage of neutrophils and the ratio of CD4 + to CD8 + were increased. Furthermore, RNI markedly enhanced the mRNA expression of TLR-9 and DNMT1, but decreased the expression of NOD2 and TRAF-6 in the ileum of piglets. In summary, postnatal nutritional restriction led to abnormal cellular and innate immune response, as well as delayed the growth and intestinal development of IUGR piglets.